Evaluating the Influence of the Presence of a Dog on Bias toward Individuals with Overweight and Obesity - Crossman, Molly K.; Kazdin, Alan E.; Galbraith, Katharine; Eros, Luca; Santos, Laurie R. (Anthrozoös, 2018)
Individuals with overweight and obesity are subject to enormous bias and discrimination across domains. This bias constitutes a considerable public health problem beyond the effects of excess weight on health. Unfortunately, the few interventions that have been implemented to reduce this bias have not been successful. Evidence that the presence of an animal makes individuals and settings appear more attractive, desirable, approachable, and relaxed, as well as happier and safer, suggests that dog ownership may be a simple way to reduce weight bias. Accordingly, we tested whether the presence of a dog can reduce weight bias in a sample of 314 online participants. Each participant was presented with a stimulus image representing one of three conditions (person with dog, person with plant, or person alone), and was then asked to rate the human model using three measures. Two sets of stimuli (featuring different models) were used to ensure that findings were not restricted to a particular model. Contrary to our predictions, we found no evidence that the presence of a dog affects endorsement of weight-related stereotypes, general evaluations, or desire for social distance. These findings contrast with a large body of literature showing that dogs enhance perceptions of a range of individuals and settings. The effect of dogs on perceptions may be restricted in the case of weight bias because of the pervasive, explicit, and severe nature of this bias. Dogs may have stronger effects on attitudes that are less openly endorsed. Promising avenues where dogs are very likely to influence attitudes include perceptions of individuals of different racial and ethnic backgrounds, gender identities, and even political parties.